2009
DOI: 10.1007/s10341-009-0080-9
|View full text |Cite
|
Sign up to set email alerts
|

Einfluss selektiver mechanischer Fruchtbehangsregulierung auf Ethylensynthese als Stressindikator sowie Ertrag und Fruchtqualität bei Kernobst

Abstract: Zusammenfassung Ziel der vorliegenden Untersuchungen war eine Verbesserung der Fruchtqualität, Brechung der Alternanz bzw. Reduzierung der Handausdünnung mit geringerem Einsatz chemischer Mittel durch mechanische Fruchtbehangsregulierung mit einer Maschine, deren drei unabhängig voneinander einstellbare Rotoren mit Schlegeln in verstellbaren Winkeln in die Baumkrone bzw. Äste eingreifen und an verschiedene Baumformen angepasst werden können. Die mechanische Fruchtbehangsregulierung erfolgte bei Blühbeginn (BBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 9 publications
1
7
1
2
Order By: Relevance
“…Effects of Mechanical Flower Thinning on the Fruit Set and Fruit Quality Attributes of 'Hongro' Apples in the trees caused by thinning, leading to an increased leaf-to-fruit ratio (Kong et al, 2009). Unlike the results here, Hehnen et al (2012) reported that the SSC in 'Buckeye Gala' apples was not improved by mechanical thinning or its combination with a chemical treatment.…”
Section: Effects Of Mechanical Thinning On Fruit Quality Attributescontrasting
confidence: 83%
“…Effects of Mechanical Flower Thinning on the Fruit Set and Fruit Quality Attributes of 'Hongro' Apples in the trees caused by thinning, leading to an increased leaf-to-fruit ratio (Kong et al, 2009). Unlike the results here, Hehnen et al (2012) reported that the SSC in 'Buckeye Gala' apples was not improved by mechanical thinning or its combination with a chemical treatment.…”
Section: Effects Of Mechanical Thinning On Fruit Quality Attributescontrasting
confidence: 83%
“…B. 'Jonagold' und 'Braeburn' kann ein zu hoher Kaliumgehalt zu verminderter Calciumaufnahme führen und damit Stippe auslösen; ein optimales K: Ca -Verhältnis in der Frucht liegt, je nach Sorte, nicht über 20-30: 1 (Kong et al 2009). …”
Section: Kaliumunclassified
“…Mechanical thinning is an effective measure for crop load management in practice (Schröder, 1996;Bertschinger et al, 1998;Damerow et al, 2007;Weibel et al, 2008;Schupp et al, 2008;Kong et al, 2009;Solomakhin and Blanke, 2010;Hehnen et al, 2012;Kon et al, 2013;Sinatsch et al, 2014;McClure and Cline, 2015;Beber, 2016;Lordan et al, 2018). An overview about the settings of the devices and al.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the intended treatment, the strings also hit et al, 2013). Therefore, it is assumed that mechanical thinning has an effect on ethylene production and export from the tissue (Kong et al, 2009), which might trigger fruit ab-ing a mechanical thinning device potentially improves fruit quality and supports return bloom the same way as chemical or mechanical hand thinning (Weibel et al, 2008;Hehnen, duction of labor input (Schupp et al, 2008). Consequently, friendly way of crop load management (Solomakhin and Blanke, 2010), which can also be applied in organic fruit production (Weibel et al, 2008;Sinatsch, 2014) and at any weather condition.…”
Section: Introductionmentioning
confidence: 99%